SYNTHESIS OF SOME NEW HETEROCYCLIC COMPOUNDS DERIVED FROM N-(Ã‘-PHENYL GLYCYL) SACCHARIN AND STUDY THEIR BIOLOGICAL ACTIVITY - Ali, Esraa M; Naser, Ahmed W.; Farhan, Muthanna S. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present work, a variety of new heterocyclic compounds namely aza-Î²- lactam, cyclicimides, 1,3-thiazole, and 1,2,4-triazole. Methods: Procedure includes the synthesis of aza-Î²- lactam, cyclic imides, 1,3-thiazole, and 1,2,4-triazole. The synthesis was carried out in eleven steps using N-(Ã‘-substituted phenylglycyl) saccharin derivatives (1a,b) as a starting material and converted to benzoic acid derivatives (2a,b) and then to ester derivatives (3a,b), which finally convers to benzohydrazide derivatives (4a,b). The cyclization of (4a,b) with carbon disulfide and hydrazine hydrate (80%) in the presence of potassium hydroxide gives 1,2,4-triazole compounds (5a,b), and subsequently (5a,b) derivatives reacted with different aromatic aldehydes in the presence of few drops of glacial acetic acid to give Schiff bases (6a-f). Compounds (7a-b) was prepared by the reaction of compounds (4a,b) with chloroacetyl chloride. 1,3-thiazole derivatives (8a,b) were synthesized through the cyclization of compounds (7a,b) with thiourea. Schiff bases (9a-f) were obtained by condensation of (4a,b) with different aromatic aldehydes in the presence of few drops of glacial acetic acid. Aza-Î²-lactam compounds (10a-f) were prepared by the cycloaddition of Schiff-bases (9a-f) with phenyl isocyanate through [2+2] cycloaddition reaction. Reaction (4a,b) with various acid anhydrides in presence of acetic acid gave the corresponding cyclic imide (11a-f). The newly prepared. Results: The results showed that compounds (5a) and (10e) have a good activity against Gram-positive bacterium and no activity against Gram-negative bacterium, compared to standard drugs (ciprofloxacin and amoxicillin), while compounds (8a) and (6b) have a high activity against fungi, compared to standard drugs (metronidazole benzoate), and the other tested compounds have low-to-moderate activity. Conclusion: 1,2,4-triazole is a most potent assemblage of Gram-positive bacterium retardants and cyclic imides are a most potent assemblage of fungi retardants.